Urinary Excretion of Ecgonine and Five Other Cocaine Metabolites Following Controlled Oral, Intravenous, Intranasal, and Smoked Administration of Cocaine - Smith, Michael L. (2010)
Urinary excretion of ecgonine (EC) was compared to that of cocaine, benzoylecgonine, ecgonine methyl ester and minor metabolites, meta-hydroxybenzoylecgonine, para-hydroxybenzoylecgonine, and norbenzoylecgonine, following controlled administration of oral, intravenous, intranasal, and smoked cocaine. Urine EC concentrations peaked later than all other analytes and had longer detection times than the other minor metabolites. With a 50 ng/mL cutoff concentration and following low doses of 10 to 45 mg cocaine by multiple routes, detection times extended up to 98 h. Maximum concentrations (Cmax) were 6–14 mole % of those for benzoylecgonine, Cmax increased with dose, time to maximum concentration (Tmax) was independent of dose, and route of administration did not have a significant impact on Cmax or Tmax for metabolites. EC is an analyte to consider for identifying cocaine use due to its stability in urine and long detection times.